1999
DOI: 10.1068/p2607
|View full text |Cite
|
Sign up to set email alerts
|

Auditory coding of visual patterns for the blind

Abstract: Recognition tasks of simple visual patterns have been used to assess an early visual--auditory sensory-substitution system, consisting of the coupling of a rough model of the human retina with an inverse model of the cochlea, by means of a pixel-frequency relationship. The potential advantage of the device, compared with previous ones, is to give the blind the ability to both localise and recognise visual patterns. Four evaluation sessions assessed the performance of twenty-four blindfolded sighted subjects us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 0 publications
6
37
0
Order By: Relevance
“…The instrumentation used in this study was based on the one of Capelle et al (1998) and Arno et al (1999). The original PSVA set-up consists of a TV camera connected to a PC including a frame grabber and a sound generation printed circuit board, itself connected to an audio ampli®er and headphones (Capelle et al, 1998).…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…The instrumentation used in this study was based on the one of Capelle et al (1998) and Arno et al (1999). The original PSVA set-up consists of a TV camera connected to a PC including a frame grabber and a sound generation printed circuit board, itself connected to an audio ampli®er and headphones (Capelle et al, 1998).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…In a previous experiment (Capelle et al, 1998;Arno et al, 1999), we have shown that trained normal blindfolded subjects can recognize simple visual patterns using a Prosthesis Substituting Vision by Audition (PSVA). The user carried on the head a miniature TV camera and a pair of headphones, both connected to a PC that simultaneously coded into sounds the images captured by the TV camera.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first system of this type is called Prosthesis Substituting Vision with Audition (PSVA) (Capelle et al, 1998;Arno et al, 1999Arno et al, , 2001. The main differences between this project and the previous one are the following: an online sonification without left-to-right scans and frequency encoding depending on both the horizontal and vertical positions of the pixels.…”
Section: Introductionmentioning
confidence: 99%
“…Another system that started slightly later is called Prosthesis Substituting Vision with Audition (PSVA) (Capelle et al, 1998;Arno et al, 1999Arno et al, , 2001. The main differences with this project compared to the previous one are an on-line sonification without left-to-right scans, and frequency encoding depending on both horizontal and vertical positions of the pixels.…”
Section: Introductionmentioning
confidence: 99%